How can fragile and conflict affected countries benefit from COP28 declarations? - Joe Y. Battikh (Anwar Gargash Diplomatic Academy, 2024)
This insight discusses the significance of the COP28 Declaration on Climate, Relief, Recovery, and Peace, which was introduced during COP28 in the UAE. This declaration is vital, as it acknowledges the complex relationship between climate change, fragility, and conflict, especially in vulnerable communities. It aims to integrate these issues into the global climate action agenda to ensure targeted and effective responses.